Modelling for changing transitive active imperative sentences to passive imperative sentences with algebraic structure approach - Yuliana Shinta; Bahri Susila; Arnawa Imade (Universitas Ahmad Dahlan, 2022)
The active imperative sentences often tend to sound harsh. The sentence has a commanding meaning and ends with an exclamation mark. In the Indonesian language, to be more polite, the sentence uses the word politeness and a different sentence structure. These more polite imperative sentences are called passive imperative sentences. Changing an active imperative sentence to a passive imperative sentence can be done mathematically through several stages. These stages are determining the set of word, and the set of word types, using binary operations to obtain the rules for changing the pronoun as an object to subject, determining the rules for substituting active verbs into passive verbs, determining algebraic structures for an active imperative sentence, specifying a set of politeness words, specifying rules for passive imperative sentence, transformation an active imperative sentence into a passive imperative sentence. The change method produces a mathematical model p to construct the more polite imperative sentence.